Research into dye-sensitized solar cells: a review highlighting progress in India. (21st June 2021) - Bera, S; Sengupta, D; Roy, S; Mukherjee, K
Abstract: In the early 1800s, the industrial revolution was powered by fossil fuels as the primary energy resource. As environmental degradation started to be felt, countries began moving toward reduced emissions and carbon-neutral footprints. Subsequently, India also began to make enormous strides in nurturing the tremendous potential of renewable energy. As it has one of the most significant energy-harvesting potentials, solar energy has remained the widely accepted choice for researchers in India. In the last few years, India has witnessed tremendous research and development in solar energy, especially in the field of photovoltaics. Significant research effort has been invested in exploring the new generation of photovoltaic devices as alternatives to traditional silicon (Si)-based solar cells. Among the various new-generation photovoltaic devices, dye-sensitized solar cells (DSSCs) remain very attractive to researchers due to their easy preparation methodology, low toxicity, and ease of production. A typical DSSC is composed of a photoanode, a sensitizer, an electrolyte, and a cathode. Various research groups in India have studied the role of each individual component within DSSCs and performed research and development activities to improve their photovoltaic efficiency. The most important part of a DSSC is the dye, which is actually the source of photoexcited electrons. This topical review will provide an overview of the research efforts undertaken in India to support the optimisation of different components of DSSCs. However, emphasis has been placed on the research activities that support the exploration of different photoactive dyes as alternatives to the N3- and N719-based organometallic dyes.